EFFECT OF CARBON SOURCES ON FORMATION OF α-AMYLASE BY BACILLUS STEAROTHERMOPHILUS - Welker, N. E. (1963)
Welker, N. E. (Western Reserve University, Cleveland, Ohio) and L. Leon Campbell. Effect of carbon sources on formation of α-amylase by Bacillus stearothermophilus. J. Bacteriol. 86:681–686. 1963.—A chemically defined medium was devised for use in α-amylase induction studies. The addition of 0.1% casein hydrolysate to the chemically defined medium permitted growth on fructose, and with glucose, sucrose, maltose, starch, and glycerol it shortened the lag period and increased both the growth rate and the total enzyme produced. Growth did not occur when gluconate, acetate, or succinate were used as carbon sources. α-Amylase was produced during the logarithmic phase of growth; the amount produced was inversely proportional to the rate of growth. The poorer the carbon source for growth (glycerol, k = 0.24; glucose, k = 0.26; sucrose, k = 0.42), the higher was the amount of enzyme produced (glycerol, 109 units/ml; glucose, 103 units/ml; sucrose, 45 units/ml). Cells grown on technical-grade maltose (k = 0.26) or starch (k = 0.42) did not conform to this relationship in that unusually large amounts of α-amylase were produced (362 and 225 units/ml, respectively). Cells grown on fructose or sucrose had the same growth rate (k = 0.42), but smaller amounts of α-amylase were produced on fructose (fructose, 0 to 4 units/ml; sucrose, 45 units/ml). An intracellular α-amylase was not detected in Bacillus stearothermophilus.